Retrospective Study to Evaluate the Anatomical variation in Proximal Branches of Great Saphenous Vein at SF Junction Encountered During Surgery for Varicose Vein - Ruchi Singh, Archana Sinha, Vanita Gupta, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background The Venous drainage of lower limb consists of Superficial and Deep venous system and the Perforators. Incompetence of valves in these veins lead to varicosities which needs surgery in form of Stripping of great saphenous vein and ligation of perforator in thigh and leg. Anatomy of lower limb veins need to be well known before proceeding for any kind of reflux surgery as there is high incidence of re-occurrence reflex if any of branches are left.